KRISIS NILAI SPIRITUAL DI MADRASAH TSANAWIYAH: ANALISIS MASALAH FUNDAMENTAL DAN ARAH REORIENTASI - Eka Lindayati; Komarudin Sassi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The phenomenon of a spiritual values crisis among students in Madrasah Tsanawiyah (Islamic junior high schools) has become a serious challenge for Islamic educational institutions in the modern era. Although MTs aims to foster religious character, the reality shows that many students experience a decline in worship commitment, weakened spiritual discipline, and a shift in values influenced by digital culture and a pragmatic lifestyle. The research used a literature study (library research) method with a qualitative approach. Data were obtained from various relevant sources, such as books, scientific journals, research articles, and Islamic education policy documents. Data analysis was conducted using content analysis techniques.This study aims to analyze the fundamental problems causing the spiritual crisis in MTs and to formulate a direction for the reorientation of Islamic education that aligns with the needs of today’s learners. The findings reveal three main factors contributing to the spiritual values crisis: (1) Islamic Education learning that remains cognitively oriented with minimal spiritual experience; (2) a lack of teacher role models and insufficiently religious school environments; and (3) weak collaboration between schools, families, and communities in nurturing Islamic values. The reorientation of Islamic education in MTs should focus on strengthening exemplary-based education (uswah), integrating tawhid-based values into all subjects, and developing continuous, context-based worship habituation programs. The reorientation of Islamic education in MTs should be directed toward reconstructing educational objectives based on maqashid sharia, strengthening the affective dimension within the curriculum, and revitalizing the roles of role modeling and spiritual habituation in the school environment. Through these efforts, Islamic education in MTs is expected to produce students who are not only intellectually competent but also spiritually and morally mature.